2020
DOI: 10.1136/bcr-2020-236950
|View full text |Cite
|
Sign up to set email alerts
|

Maternal complications of fetal triploidy: a case report

Abstract: A 32-year-old woman underwent a medical termination in the second trimester of a spontaneously conceived triploid pregnancy after developing early-onset preeclampsia with subsequent haemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome. Placental histology was normal (non-molar) and unusually, she developed ovarian hyperstimulation syndrome (OHSS) 4 weeks later. She was managed conservatively following multidisciplinary team input to exclude malignant pathology. The rarity of late-onset s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…An overlapping etiology with molar pregnancies has been suggested as placental studies in pregnancies complicated by triploidy and preeclampsia have revealed hydropic and hydatidiform molar degeneration [ 8 , 9 ]. This is further evident by the commonly accompanying sonographic appearance of placentomegaly and markedly elevated maternal serum free β-human chorionic gonadotropin (β-hCG) in affected pregnancies [ 3 , 8 ], both of which were present in this case.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…An overlapping etiology with molar pregnancies has been suggested as placental studies in pregnancies complicated by triploidy and preeclampsia have revealed hydropic and hydatidiform molar degeneration [ 8 , 9 ]. This is further evident by the commonly accompanying sonographic appearance of placentomegaly and markedly elevated maternal serum free β-human chorionic gonadotropin (β-hCG) in affected pregnancies [ 3 , 8 ], both of which were present in this case.…”
Section: Discussionmentioning
confidence: 60%
“…digynic) or paternal (i.e. diandric) in origin [ 3 , 4 ]. Given that triploidy is not compatible with life, most affected pregnancies will result in an early first-trimester loss [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interpretation is that the involved physicians focused on the reasons for the referral and less on general screening options. However, pregnancies with increased nuchal translucency, increased risk of aneuploidies at screening and diagnosed genetic anomalies such as trisomy 13 are found to be at increased risk of preeclampsia if the pregnancy is continued 23 , 24 , 25 , 26 . Another explanation could be that some doctors are less convinced that PE screening is useful.…”
Section: Discussionmentioning
confidence: 99%
“…Penurunan tekanan darah yang paling baik pada kasus dengan Pre Eklampsia adalah 25-30% dari tekanan darah sebelum dilakukan terminasi tetapi pada usia kehamilan kurang bulan sebagian besar hanya mengalami penurunan tekanan darah diastolik sebesar 10 mmHg. Sesuai dengan pendapat dari Wali & Wild (2020) pada kasus Pre Eklampsia Ringan yang dalam perawatan unresponsive terhadap pengobatan atau ada tanda bahkan impending Eklampsia, Eklampsia dan IUGR harus segera dilakukan terminasi. Hal inilah yang menyebabkan proses pemulihan yang salah satu indikatornya adalah penurunan tekanan darah akan membutuhkan waktu yang lebih lama (Sacks et al, 2018).…”
Section: Pembahasanunclassified